DESCRIPTION AND MAPPING OF URBANIZATION DEVELOPMENT IN SUMATERA UTARA - Nurhanifah Nurhanifah (JURNAL GEOGRAFI, 2021)
The number of urban residents continues to increase each year due to the mobility of the population from villages to cities (urbanization). Aims this article  to describe the development of urbanization in North Sumatra. Method of research is library research, data collection is carried out by taking from various sources such as BPS data, journals, documentation, and coupled with observational data then analyzed descriptively. This research found  that the population development of North Sumatra (North Sumatra) is still concentrated in Medan City. Although its geographical area is only 0.36% of North Sumatra's area, Medan is inhabited by 2,279,894 million people. The concentration of the population of North Sumatra in Medan is due to the ongoing urbanization or migration of people from villages to cities. The high number of urban residents can be a problem for the government, one of which is the emergence of the phenomenon of poverty, homelessness, and congestion. Often people who move to urban areas have big reasons and expectations such as wanting to get a job, high wages, prestige, and wanting to enjoy urban facilities. The conclusion is the development of the urban population in North Sumatra is in line with the rapid development of infrastructure, such as toll roads, and industries built by the government or the private sector continue to grow. The increasing level of urbanization shows the increasing number of people living in urban areas (cities) which causes the population to become denser in urban areas. The large number of people who urbanize in North Sumatra is due to economic and social factors.Keywords: Urbanization, Mapping, Development, Nort Sumatra